(untitled) (Research, Society and Development, 2021)
Introduction: Knowledge about Basic Life Support (BLS) can save lives. Objective: To evaluate the knowledge of students in the technical course in nursing before and after theoretical training on BLS in adults. Materials and Methods: Quasi-experimental study carried out with 74 students of the technical nursing course at an educational institution in Minas Gerais. The measurement of sociodemographic variables and knowledge about BLS was carried out using a previously validated questionnaire. Using the IBM ® SPSS 23.0 software, the Mcnenar and Wilcoxon tests were used to compare the proportion of correct answers and the median level of knowledge. Results: The median knowledge of students after training was significantly higher than in the pre-test (p <0.001). However, the issues that involved triggering the urgency / emergency service and performing cardiopulmonary resuscitation were the only ones that showed a significant increase in the number of correct answers. Discussion: Theoretical training was able to increase the knowledge of students of the technical course in nursing, however, only in the questions that involved the initial links of the survival chain can a significant increase be observed. Conclusion: the theoretical training contributed to the apprehension of content, improving the cognitive capacity of the participants.